Phytohormonal balance in leaves of the soft wheat lines isogenic for VRN genes - Avksentieva, O. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2023)
The paper presents results of the study of the phytohormonal balance in mature, formed leaves of the lines of common wheat (Triticum aestivum L.) of the winter variety Olvia during the transition from vegetative to generative development. Near isogenic for the VRN genes lines (NILs) created in the gene pool of the Olvia variety and plants of the vernalized and non-vernalized winter variety were used. The experiments were carried out under the conditions of a vegetation experiment in the factorial chamber of the Department of Physiology and Biochemistry of Plants and Microorganisms of the V.N. Karazin KhNU. During the experiment, we conducted physiological observations and analyzed the development rate of experimental plants. Phytohormone analysis was carried out in fixed plant material by a chromatographic distribution of phytohormone mixture with thin-layer chromatography. The phytohormones were identified by the reference standards irradiating the chromatograms with ultraviolet UV (254 nm), and the content was determined by biotesting methods. The level of main classes of classical growth-stimulating phytohormones (auxins (IAA), cytokinins (CK), and gibberellins (GA), and growth-inhibiting hormones (abscisins (ABA)) was analyzed. The indicators of phytohormonal balance were calculated as the ratio of growth-stimulating and growth-inhibiting hormones. The results of the experiments showed that phytohormones in mature, formed leaves of the experimental plants are represented by auxins – 64.9-70.7 μg/g, cytokinins – 26.6-30.5 μg/g, gibberellins – 179.47-228.68 μg/g, and abscisins – 54.06-89.76 μg/g of dry weight. Among the phytohormone classes studied, the minimal was the cytokinins’ content, while the phytohormones of terpenoid nature (gibberellins and abscisins) were represented best. It has been established that the phytohormonal balance viz. the ratio of growth-stimulating and growth-inhibiting phytohormones reflects the development rate of experimental plants. Rapidly developing plants of isolines VRN 1 and VRN 3, and the plants of vernalized variety were characterized by the maximum phytohormone balance (especially GA/ABA), while the slowly developing plants of the isoline VRN 2 and the non-vernalized variety Olvia had the minimum balance. Since the plant organism is an integrated system of organs and functions, we assume that this indicator – phytohormonal balance in plant leaves, can be used as a marker of the ontogenetic state of the entire plant organism. The identified changes in the phytohormonal status of mature, formed leaves and the development rates of experimental plants have the same regularities in all the models used in our research: the model of isogenic lines and the model of vernalized and non-vernalized plants of the winter variety. This fact makes it possible to assume that changes in the phytohormone balance of mature leaves, which reflect the ontogenetic state of the entire plant organism, are determined by the genotypic and phenotypic (epigenetic) influence.